Un acercamiento a la vigencia de la anagnórisis en el efecto final del cuento - Rosa de Viña Carmona (Recherches)
The aim of this article is to apply the concept of anagnorisis, taken from Aristotle, to the construction of the plot of the fantastic tale in order to trace its validity from the birth of the tale and the first poetics with Edgar Allan Poe up to the modern and contemporary tale. The narrative scheme proposed in tales by Edgar Allan Poe, Théophile Gautier, Horacio Quiroga and Carlos Fuentes will be seen in order to exemplify the proposal that every anagnorisis within the tale entails a fulfilled fatality that is nothing but an approach to death.